Role of Trademark in Improving Legal and Competitive Awareness - Endang Purwaningsih (LAW REFORM, 2020)
There are a lot of traditional food producers in Brebes Regency but they have not been managed well. Many obstacles were experienced by these MSMEs producers, including the problem of the ignorance of trademark registration, and the mindset and motivation that need to be addressed. The purpose of this study was to determine the level of knowledge of traditional food producers on trademarks and the motivation of traditional food producers in Brebes Regency for trademark registration in an effort to increase their legal awareness and competitive awareness. The research method used was empirical juridical research that emphasizes secondary data balanced by primary data as a support. The results show that the knowledge level of the traditional food producers in Brebes Regency towards trademarks was still low, and it needs to be improved with various socialization on trademark manufacturing, trademark registration, and branding assistance. The mindset and motivation of Brebes Regency traditional food producers towards trademark registration in an effort to increase legal awareness and competitive awareness is still low, so it needs to be improved and addressed. In addition, it is also necessary to be accompanied continuously by the stakeholders; in this case, the producer organization (MSMEs Forum) and related agencies in the area.